Compliance with the Malaysian National critical practice guidelines on the administration of thrombolytic agents in acute st-elevation myocardial infarction - SMS, Azarisman; Ngow, Harris Abdullah; PA, Melor; Ab Rahman, Jamalludin; Ahmad, Fauzi@Fauri; Satwi, Sapari; K., Khairi; S, Noorfaizan; Maskon, Oteh (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Background In developing countries such as Malaysia, the primary mode for revascularization is via thrombolytic therapy. In 2001, the 1st Edition of the Malaysian Clinical Practice Guideline advised the door-to-needle time of 60 minutes. This has been revised in the 2nd Edition (2007) to 30 minutes. This study aims to evaluate the mean door-to-needle times following the implementation of Emergency Department-based thrombolysis. Methods Accident and Emergency-based (AE) thrombolysis was initiated at Hospital Tengku Ampuan Afzan Kuantan, Malaysia. Ninety four patients with acute ST elevation myocardial infarction patients were screened and 75 patients were recruited. The mean house-to-door, door-to-needle times were recorded. Results The majority of patients were male (89.3%), of Malay ethnicity (84%), presenting with anterior MI (69.3%) with a mean age of 57.0 9.52 years. The mean door-to-needle time was 80.54 84.8 minutes (116.46 109.00 minutes before the implementation). Only 20% achieved the 30-minute door-to-needle time and only 65.3% achieved the 60 minute door-to-needle time. The reasons for late thrombolysis were quoted as late referrals from AE (50%), hypertensive emergency (22%), resuscitation (17%) and others (11%). Conclusion Implementation of Emergency-based thrombolysis has improved the door-to-needle times but more staff education and training is required due to the high rate ofblate AE identification and late referrals.